Makna Hanabi Dalam Lagu Jepang - Wahyuni, Kadek Ari; Andry Anita Dewi, Ni Made; Ari Sulatri, Ni Luh Putu (Humanis; Volume 17. No. 2. Nopember 2016, 2016)
The title of thi s research is “ The Significance of Hanabi in Japanese Songs ” . Th is research aims to analyz e the depictions and the significance of hanabi in four Japanese Songs; Utakata Hanabi by Ryo, Hanabi by Her0ism, Boku no Uchiage Hanabi by Yasushi Akimoto, and Hanabi by Kanichi Shimofusa. The theories that are used for analyzing are literary anthropology by Endraswara (2008) and semiotics by Riffaterre (1978). The results of this research showed that in the four songs, hanabi was depicted as part of Japanese cultures and become an annual tradition that continues celebrated every summer. Also, it was found that the significance of hanabi in each song is different.